Does Practice Make a Translator? the Impact of Translation Practice in Students’ Self-Efficacy Beliefs [la Pratique Fait-Elle Le Traducteur ? L’Impact de la Pratique de la Traduction Sur Les Croyances D’Auto-Efficacité Des Étudiants] [¿La Práctica Hace Al Traductor? el Impacto de la Práctica de Traducción en Las Creencias de Autoeficacia de Los Estudiantes] - Singer-Contreras, N (Universidad de Antioquia, 2022)
Researchers have been increasingly interested in exploring translators’ self-efficacy beliefs in recent years. However, from a pedagogical perspective further research is needed. This article aims to analyse how professional internships by translation students from three translator education programmes —two offered in Chilean universities (Universidad de Santiago de Chile and Pontificia Universidad Católica de Valparaíso) and one offered at a Spanish university (Universidad de Granada)— influenced students’ self-efficacy beliefs. The participant students’ perceptions were collected as part of two doctoral research works. Both research projects followed qualitative methodology, relying upon both group and individual interviews. The resulting audio material was transcribed and thematically analysed following guidelines from grounded theory. Results show that professional practice during translator education seems to be essential for the development of translator students’ self-efficacy beliefs, irrespective of the translator educational setting they are immersed (Chile and Spain). Thus, we can conclude that this study is an empirical contribution to the understanding of self-efficacy beliefs in translator education. © 2022 Universidad de Antioquia. All rights reserved.